Economic foundations of private law - Parisi, Francesco; Posner, Richard A. (Cheltenham, UK ; Northampton, MA : E. Elgar, 2002)
This book is a collection of seminal papers on law and economics, economics of property, contracts and torts.
Includes bibliographical references and name index.
lje 29/04/13, ijb 28/03/2019
Loan
Keywords: Law and economics; Civil law